Synbiotic Therapy Prevents Nosocomial Infection in Critically Ill Adult Patients: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials Based on a Bayesian Framework - Li, Cong; Liu, Ling; Gao, Zhiwei; Zhang, Junwei; Chen, Hui; Ma, Shaolei; Liu, Airan; Mo, Min; Wu, Changde; Chen, Dongyu; Liu, Songqiao; Xie, Jianfeng; et al. (Frontiers in Medicine, 2021)
Background: The efficacy of synbiotics, probiotics, prebiotics, enteral nutrition or adjuvant peripheral parenteral nutrition (EPN) and total parenteral nutrition (TPN) in preventing nosocomial infection (NI) in critically ill adults has been questioned. We conducted a systematic review and network meta-analysis (NMA) of randomized controlled trials (RCTs) to evaluate and rank the effectiveness of these therapies on NI amongst critically ill adults. Methods: Four electronic databases were systematically searched up to June 30, 2019 for RCTs comparing the administration of probiotics, prebiotics, synbiotics, EPN and TPN in critically ill adults. The primary outcome was NI. The relative efficacy of all outcomes was determined by a Bayesian framework with random effects NMA. We estimated the odds ratio (OR) and mean difference (MD) and ranked the comparative effects of all regimens with the surface under the cumulative ranking probabilities. The study has been registered on PROSPERO (CRD42019147032). Results: Fifty-five RCTs (7119 patients) were identified. Primary outcome showed that synbiotics had the best effect in preventing NI than EPN (OR 0.37; 95% CrI 0.22-0.61), probiotics followed (OR 0.52; 95% CrI 0.34-0.77), whereas TPN significantly increased NI (OR 2.29; 95% CrI 1.48-3.67). Subgroup analysis showed that TPN significantly increased NI in intensive care unit (ICU) patients (OR 1.57; 95% CrI 1.01-2.56) and severe acute pancreatitis (SAP) patients (OR 3.93; 95% CrI 1.74-9.15). Secondary outcomes showed that synbiotics were more effective in preventing hospital-acquired pneumonia (HAP) (OR 0.34; 95% CrI 0.11-0.85), catheter-related bloodstream infection (OR 0.08; 95% CrI 0.01-0.80), urinary tract infection (OR 0.27; 95% CrI 0.08-0.71) and sepsis (OR 0.34; 95% CrI 0.16-0.70) than EPN. Amongst the treatments, probiotics were most effective for shortening the mechanical ventilation duration (MD -3.93; 95% CrI -7.98 -¬¬ -0.02), prebiotics were most effective for preventing diarrhea (OR 0.24; 95% CrI 0.05-0.94) and TPN was the least effective in shortening hospital length of stay (MD 4.23; 95% CrI 0.97-7.33). Conclusions: Amongst the five therapies, synbiotics not only prevented NI in critically ill adults but also demonstrated the best treatment results. By contrast, TPN did not prevent NI and ranked last, especially in ICU and SAP patients.